L’album sans texte : de la répétition à la narration - Valérie Ducrot (Strenae)
In 1968, Little Blue and Litte Yellow, a cultural object for school children by nature, was published. This picture book was the pioneer of narrative picture book without a displayed text, a new category of children’s books thus distinguisable from other picture books and alphabet books. Those were seen as books intended for a non-reading public for a long time because they had no text. Today’s editorial line shows that these picture books have left the field of simplistic narratives aimed at young children to enter that of picture books with a non-straightaway-accessible meaning.Not only does this category of picture books, commonly called « silent books », enables us to question a new form of literary poetry, but it also allows some didactic practices such as adult-scribed storytelling. This article proposes to look into some distinctive poetical traits of that new litterary object in order to show how new didactic practices can be fixed beyond pre-kindergarten. The analysis of two contemporary authors, Anne Brouillard and Suzy Lee, based on researches by R. Baroni, S. Martin and R. Goigoux, will permit to discover how this category brings a fresh didactic perspective to the introduction of reading as soon as preschool.Thus, with the works of Anne Brouillard and Suzy Lee, a particular attention will be paid to the phenomena of repetition. Then, this perspective allows to question a recurring teaching practice , that is to say adult-scribed narrative.